Meningkatkan Kemampuan Berpikir Kritis Matematis Siswa SMK melalui Model Pembelajaran Berbasis Masalah - Marwan Marwan; M. Ikhsan; Marwan Marwan (Didaktik Matematika, 2016)
Mathematics is a subject that can train students in developing critical thinking, logical, creative, effective and systematic as well as assist in the development of personality and reasoning power of a person. Hopefully, with these capabilities that students can face all kinds of challenges in today's modern era. This study aims to determine the increase in critical thinking skills students acquire mathematical learning with problem based learning model in terms of: (a) the whole student, and (b) the level (high, medium, and low) ability of students. This study uses a quantitative approach with the experimental method. The population in this study are all class XI student of SMK Negeri 5 Banda Aceh and a sample of the research is class XI RPL-1 as an experimental class and class XI RPL-2 as the control class. The data were analyzed with the average gain is normalized between the two classes. The results showed that an increase in the ability of critical thinking mathematical students acquire learning with problem based learning model is singnifikansi better than on the ability of critical thinking mathematical students who received conventional learning when viewed from the overall and by level (high, medium, and low) ability of students.